Regional risk of tuberculosis and viral hepatitis with tumor necrosis factor-alpha inhibitor treatment: A systematic review - Jahnich, Nina; Arkwright, Peter D. (Frontiers in Pharmacology, 2023)
Background: TNFα inhibitors are regularly used to treat autoimmune diseases. Tuberculosis (TB) and viral hepatitis B are considered potential infectious complications, and screening and surveillance are therefore recommended. Current guidelines do not take into account regional differences in endemicity of these infections. Methods: A systematic literature review of TB and viral hepatitis in patients receiving TNFα-inhibitors was performed, searching in PubMed, Embase, MEDLINE and Web of Science databases. Studies were selected against predefined eligibility criteria and assessed using the Newcastle-Ottawa scale. The number of TB and viral hepatitis cases/1,000 TNFα-inhibitor patients were evaluated, and regional variation compared. Results: 105 observational studies involving over 140,000 patients were included. Overall, 1% of patients developed TB or viral hepatitis B. TB cases/1,000 TNFα-inhibitor patients were 4-fold higher in Asia, Africa, and South America than in Europe, North America, and Australasia where only 0 - 0.4% of patients developed TB. Hepatitis B cases/1,000 patients were over 15-fold higher in countries with high prevalence (China, Taiwan, South Korea, Thailand) compared with low prevalence (p<0.00001) where only 0.4% of patients developed hepatitis B. Only three of 143 patients developed viral hepatitis C, and there was insufficient data to allow regional sub-analysis. Conclusions: TB and viral hepatitis B infections in patients treated with TNFα inhibitors are largely confined to countries with high prevalence of these infections. As only 1/2,500 patients in low prevalence countries treated with TNFα inhibitors develop TB or viral hepatitis B, we suggest an individualized, risk-based approach, rather than universal screening for all patients.